The Implementation of Prenatal Exercise to Reduce Back Pain in Third Trimester Pregnant Women - Fisca Jevanesia, Nawa; Roslianti, Elis (Genius Midwifery Journal, 2025)
Background: Pregnancy is a physiological process that induces various bodily changes in women, including hormonal, postural, and biomechanical adaptations. Back pain is a common complaint among pregnant women, particularly during the third trimester. Prenatal exercise serves as a non-pharmacological intervention designed to enhance physical fitness, strengthen muscles, and alleviate pregnancy-related discomfort. Objective: This case study examines the implementation of prenatal exercise to reduce back pain in Mrs. Y, a third-trimester pregnant woman in Banjarsari District, Ciamis Regency. Method: Using a qualitative descriptive methodology with a maternity nursing care process approach (assessment, nursing diagnosis, planning, implementation, and evaluation), data were collected through interviews, physical examinations, observations, and documentation review. Result: Initial assessment revealed Mrs. Y experienced intermittent back pain described as "heavy pressure" with radiating characteristics, aggravated by activity and relieved by rest. The intervention involved three consecutive days of guided prenatal exercises, with pain intensity monitored using the Numeric Rating Scale (NRS). Results demonstrated reduced pain intensity (from moderate to mild), improved sleep quality, better posture, and enhanced overall comfort. Additionally, the subject showed increased readiness for childbirth. Conclusion: This study concludes that prenatal exercise is a safe and effective method for mitigating back pain and should be integrated as a promotive-preventive strategy in maternity nursing care. The author recommends incorporating prenatal exercises into standard antenatal class programs at primary healthcare facilities